The D-domain of fibrin : structural and functional studies - Purves, Maud (Division of Chemical Pathology, 2018)
The D-domain of fibrin (ogen) was separated from the parent molecule by plasmin digestion in the presence of calcium and isolated by means of DEAE-anion exchange chromatography followed by gel-filtration in buffer containing 4 M urea. Fluorescent-D-dimer (f-D-dimer) was isolated from a plasmic digest of fibrin clotted in the presence of 2.45 mM dansyl cadaverine, a fluorescent lysine analogue. Fluorescent-D-monomer was a by-product of f-D-dimer purification, the yield being determined by the concentration of dansyl cadaverine. At 2.45 mM f-D-monomer was always present in the digest. The f-D-monomer is probably formed directly and not as a result of degradation of f-D-dimer. The molecule elutes in the fibrinogen-derived-D- monomer position on gel-filtration. A protease was isolated and partially purified from venom of the puffadder (Bitis arietans). Puffadder venom protease is characterized by its ability to cleave D-dimer into symmetrical D-monomers, smaller than plasmin-derived D-monomers from fibrinogen. This characteristic was used to detect the puffadder venom protease activity with fluorescent-D-dimer being used as the substrate. Fractions obtained were assayed for D-dimer cleavage activity and the samples analyzed by means of SDS-PAGE on 4-20% gradient gels under reducing (βME) and non-reducing conditions. The fluorescent bands were located under U.V light and photographed prior to staining with Coomassie Blue. Several methods for the purification of the protease were investigated.